Pembekalan Kompetensi Siswa Mengikuti Uji Kompetensi Bidang Multimedia bagi Siswa SMKN 1 Payung - Hamidah Hamidah; Okkita Rizan; Sujono Sujono; Harrizki Arie Pradana (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
Technological developments are increasingly developing. This requires students to improve skills in the field of multimedia to assist in dealing with school competency tests. All students are expected to be able to take the test and are required to pass as one of the graduation requirements. In this pandemic era, learning activities were a little disrupted so that it demanded that the school provide maximum provision for students. SMKN 1 Payung students still do not understand how to apply multimedia. Based on the above problems, it is necessary to provide provision on multimedia so that students are ready to face school competency exams. Some applications that can be used as a tool for creating multimedia are the Corel Draw X7 application specifically for designing multimedia and Adobe Illustrator for creating animations. The method used in this provision is direct multimedia design practice. It is hoped that this debriefing activity can improve the abilities of all students in facing competency tests so that they can graduate on time.